Hubert M. Blalock Jr. Causal inferences in non-experimental research. Chapel Hill, [N. C.] : The University of North Carolina Press, 1964. ix, 200 p. - Reyna, José Luis (Estudios Demográficos y Urbanos, 1969)
HUBERT M. BLALOCK Jr., Causal Inferences in Non-Experimental Research. Chapel Hill, The University of North Carolina Press, 1964.